Alcoholist Attedance Program: 30 years of education-Assistance, Research and University and Extension - da Silva de Andrade, Laerson; de Oliveira Seabra, Larissa; Bezerra de Oliveira, Larissa; Albane, Sibele; Queiroz Subrinho, Lucas; Portugal, Flávia Batista; Mechelli de Siqueira, Marluce (Guará Journal, 2018)
Harmful alcohol consumption is one of the main factors for morbidity and mortality and worldwide. In this sense, the Alcoholism Attendance Program of the Cassiano Antônio Moraes Hospital of the Federal University of Espírito Santo was created in 1985. In 1987, it became an extension program and in these 30 years the Alcoholism Assistance Program is a reference in outpatient care. This is an observational, descriptive and exploratory study. It is based on the observation of the consultations carried out and documental analysis of the productions made by the professionals involved in the process of assisting alcoholics and family members. The university extension program seeks to articulate teaching, professional training and assistance. The study may contribute to the replication of the successful actions of PAA-HUCAM-UFES in the state of Espírito Santo and help to build new care practices and training professionals to serve the alcohol consumer